Hospitality sales a marketing approach - Shaw, Margaret 1949- (Wiley, 1999)
What It Takes to be a Leader in Hospitality Sales-Principles and Techniques for Success What's the key to success in today's competitive hospitality industry? Sales-the art and science of telling potential customers that you have the product they need, when they need it, and where, at a price that's right for them. Hospitality Sales: A Marketing Approach provides in-depth instruction based on the strategies of leading hospitality organizations. This comprehensive book introduces crucial sales and marketing concepts and describes how they apply to hospitality businesses and customers. An unparalleled teaching resource, this book: Presents selling as the vital link between marketing and operations Explains concepts and practices with clear, real-world examples Explores sales management technology, from office automation and yield management technology to point-of-sale systems and guest service technology Provides summaries and discussion questions at the end of each chapter Features a quick-reference glossary of important terms Hospitality Sales: A Marketing Approach introduces students in any undergraduate program to the real world of hospitality sales and gives them the solid grounding they will need to embark on a successful career in hospitality sales.